2018
DOI: 10.1021/acs.analchem.8b03850
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Heterostructured CuFe@FeFe Prussian Blue Analogue Coupling with Silver Nanoclusters via a One-Step Bioinspired Approach: Efficiently Nonlabeled Aptasensor for Detection of Bleomycin in Various Aqueous Environments

Abstract: We synthesized novel core−shell heterostructured Prussian blue analogue (PBA) nanospheres coupled with silver nanoclusters (AgNCs) via a one-step bioinspired approach and further exploited these as aptasensors for the detection of a trace antibiotic, bleomycin (BLM). Using FeFe Prussian blue (FeFe PB) as the core, a bimetallic CuFe@FeFe PBA layer was prepared by coupling with AgNCs synthesized by taking the BLM-targeted aptamer as a template (denoted by AgNCs/Apt@CuFe@FeFe). The coupling of AgNCs/Apt via a one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In these cases, the dried particles were either purchased ( 39 , 40 ), or isolated from the reaction suspension applying centrifugation ( 41 , 42 ), magnet separation ( 43 ), electrodeposition ( 34 , 44 ) or solution drying techniques ( 45 , 46 ). Furthermore, crystalline nanosilver product can also be obtained by implementing precipitation agents ( 35 , 47 ). Recently, we have shown that weak organic acids ( 48 ), as well as strong mineral acids ( 49 ), can be successfully applied to precipitate polyacid-stabilised nanosilver grains as the functional component of printable conductive inks.…”
Section: Synthesis Of Silver Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these cases, the dried particles were either purchased ( 39 , 40 ), or isolated from the reaction suspension applying centrifugation ( 41 , 42 ), magnet separation ( 43 ), electrodeposition ( 34 , 44 ) or solution drying techniques ( 45 , 46 ). Furthermore, crystalline nanosilver product can also be obtained by implementing precipitation agents ( 35 , 47 ). Recently, we have shown that weak organic acids ( 48 ), as well as strong mineral acids ( 49 ), can be successfully applied to precipitate polyacid-stabilised nanosilver grains as the functional component of printable conductive inks.…”
Section: Synthesis Of Silver Nanomaterialsmentioning
confidence: 99%
“…A current trend in the sensor field is directed towards solving analytical problems with the development of cost-effective, miniaturised and portable devices that could be operated in the field ( 54 ). A survey of the silver nanomaterial-based electrochemical sensors for food applications published in the last five years is listed in Table 1 ( 32 , 34 , 35 , 39 , 40 , 44 , 45 , 47 , 55 - 85 ). Selected examples of electrochemical sensors, both voltammetric and impedimetric, are shown in Fig.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Core-shell heterostructured PBA nanospheres were composited with silver nanoclusters and further applied as aptasensors for detecting bleomycin. 30 Especially, PBA nanocube precursors containing different metal ion centers such as nickel, cobalt, and iron were used to keep a general nanocuboidal structure while optimizing the composition of metal centers to efficiently anchor the probe biomolecules. Nevertheless, PBA-based biosensors for detecting EGFR have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one-step electrochemical biosensors have attracted considerable interest, due to their promising application in the medical diagnostics, food safety fields, and environmental monitoring. [32][33][34] Up to now, one-step aptasensors for Pb 2+ are rarely reported. 35 In order to improve the reliability of detection results, dual-mode detection has attracted much attention in recent years.…”
mentioning
confidence: 99%